Performance of Powder mixed Drilling EDM on Biomedical Ti-6Al-4V Alloy - Nurlan Nauryz; Salikh Omarov; Didier Talamona; Asma Perveen (EDP Sciences, 2023)
Titanium alloys have gained a lot of attention in biomedical due to their novel properties. In fact, their low elastic modulus and good biocompatibility have promising potential in load bearing bone replacement implants. However, a big part of successful implantation relies on proper surface treatment, which can enhance its performance. Electro discharge machining (EDM) is one of the surface treatment techniques that can be beneficial for proper surface forming. For that reason, this study investigates the machining conditions of EDM on Ti-6Al-4V titanium alloy. In details, this paper evaluates the effect of machining parameters of pulse current, time-on, time-off, gap voltage and powder on material removal rate (MRR) and overcut. Moreover, an experiment set based on L9(34) Taguchi’s orthogonal array was conducted and the analysis of variance was observed. In order to investigate the optimum machining condition, grey relation analysis (GRA) and analysis of variance (ANOVA) were used. In conclusion, the best performance parameters for MRR, overcut and multiple characteristics of the orthogonal array were observed and predicted improvements are calculated in this paper.
Keywords: Machining; Titanium alloy; Materials science; Orthogonal array; Electrical discharge machining; Taguchi methods; Alloy; Titanium; Mechanical engineering; Metallurgy; Composite material; Engineering; type of access: open access